Validation of pharmaceutical information systems: databases and laboratory information management systems - K. A. Koshechkin; E. V. Gladkaya; Ya. Yu. Kondratieva (Регуляторные исследования и экспертиза лекарственных средств, 2018)
The article describes the basic principles of validation of the databases and laboratory information management systems used by pharmaceutical organizations. The principles are arranged on the basis of international OMCL network requirements and ISO standards. The article presents the general approaches to validation of these types of information systems and evaluation of soft- and hardware choices, and the requirements to the procedure of installation and the settings of those. It contains the requirements to test data sets and general methodology for conducting the validation tests. Additionally, it covers the possibility to validate not only new software, but also the software currently in use.